Plastic ingestion by Atlantic cod (Gadus morhua) from the Norwegian coast - Brate, Inger Lise N.; Eidsvoll, David P.; Steindal, Calin Constantin; Thomas, Kevin V. (Marine Pollution Bulletin, 2016)
This study documents the occurrence of microplastic (< 5 mm), mesoplastics (5–20 mm) and macroplastic (> 20 mm) in Atlantic cod (Gadus morhua), a common and economically important species of marine fish in Norway. Fish stomachs (n = 302) were examined from six different locations along the coast of Norway. Three percent of the individual stomachs contained items identified by Fourier transform infrared spectroscopy (FTIR) as synthetic polymers. Bergen City Harbour was a hotspot with 27% of the cod examined found to contain plastic. Polyester was the most frequently detected polymer. All bar one of the stomachs that contained plastic were full of organic stomach content, suggesting a plastic gut clearance rate similar to the ingested food. It is proposed that stomach fullness is an important metric in order to avoid underestimations when assessing the levels of microplastic ingested by fish.